PERUBAHAN TINGKAT PENAWARAN BARANG SEMBAKO PADA TAHUN 2023 DI TOKO IJO SANGATTA - Aprilia, Diva; Anjani, Maulidiah; Nuraulia, Maya; Afriani, Syafira; Zulkadrin, Zulkadrin (At-Tawazun, Jurnal Ekonomi Syariah, 2024)
This study aims to analyze the factors that cause fluctuations in the supply of basic necessities at Toko Ijo, Sangatta, East Kalimantan, throughout 2023. The research method used is qualitative with a descriptive approach, which aims to comprehensively examine changes in the level of supply of basic necessities. Research data was obtained through interviews, observations, and documentation to explore information about goods ordering policies, sales strategies, and challenges faced in stock management. The results of the study show that fluctuations in the supply of basic necessities at Toko Ijo are influenced by internal and external factors. External factors include the harvest season, seasonal demand during Ramadan and Eid al-Fitr, as well as the availability of supply from distributors. Meanwhile, internal factors include stock management and store operating costs. Data analysis shows that there is a fluctuating trend in the supply of goods, especially rice, throughout the year. The decline in supply occurred in the first quarter due to the famine season, while the increase occurred in the second quarter in line with the harvest season and a surge in demand ahead of Ramadan. The third quarter showed a decline again, while the fourth quarter tended to be stable and increased ahead of the year-end holidays.